2012
DOI: 10.1242/dev.076497
|View full text |Cite
|
Sign up to set email alerts
|

Failure of extra-embryonic progenitor maintenance in the absence of dosage compensation

Abstract: SUMMARYProper regulation of X-linked gene expression, termed dosage compensation, is required for the normal development of mammalian embryos. Through the process of X chromosome inactivation (XCI), somatic cells of mammalian females inactivate one of their two X chromosomes in order to balance X-linked gene dosage with their male counterparts. The process of XCI is dependent upon the long non-coding RNA Xist, which is expressed from and coats the inactivated X chromosome (Xi) in cis. During mouse embryogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…Lack of imprinted XCI is supported by studies in rabbit parthenogenotes, and in human and horse placenta 34,50 . By contrast, early X silencing seems to be essential in mice to quickly ensure correct dosage given fast embryonic development 51 . Comparisons between mice and humans with sex chromosome aneuploidy also highlight the importance of early paternal X silencing in mice: only XmXpY (where Xm denotes the maternal X chromosome and Xp the paternal X chromosome), but not XmXmY, karyotypes survive in rodents 52 , whereas equal percentages of these karyotypes are observed in humans 53 .…”
Section: Variable XCI Initiation and Mosaic X Expressionmentioning
confidence: 96%
“…Lack of imprinted XCI is supported by studies in rabbit parthenogenotes, and in human and horse placenta 34,50 . By contrast, early X silencing seems to be essential in mice to quickly ensure correct dosage given fast embryonic development 51 . Comparisons between mice and humans with sex chromosome aneuploidy also highlight the importance of early paternal X silencing in mice: only XmXpY (where Xm denotes the maternal X chromosome and Xp the paternal X chromosome), but not XmXmY, karyotypes survive in rodents 52 , whereas equal percentages of these karyotypes are observed in humans 53 .…”
Section: Variable XCI Initiation and Mosaic X Expressionmentioning
confidence: 96%
“…A recent study (Mugford et al, 2012) reported that the poor trophectoderm development in E6.5 embryos with a paternal Xist deletion is due to premature differentiation and depletion of Cdx2-positive trophoblast progenitors, rather than to TGC growth and differentiation defects. However, another study (Hoki et al, 2011) showed that the development of secondary TGCs is impaired in the context of an Xist hypomorph that survives to E12.5.…”
Section: Research Articlementioning
confidence: 99%
“…XCI first takes place with a bias to silencing the paternal X chromosome (Xp) during preimplantation stages (imprinted XCI) and is maintained in the trophectoderm and primitive endoderm lineages (Takagi and Sasaki, 1975). The absence of dosage compensation causes an arrest in proliferation of the progenitor cells of the trophoblast and results in the failure of placental differentiation (Mugford et al, 2012;Roberts et al, 2004). It is likely that the defects in the extraembryonic tissues lead to deterioration in the subsequent development of embryonic tissues (Takagi and Abe, 1990).…”
Section: Introductionmentioning
confidence: 99%